Comparing the Effectiveness of Hashtags in Digital Social Movements: A Case Study of #PercumaLaporPolisi and #PolriSesuaiProsedur in Indonesia - Zuraida, Zuraida (CHANNEL: Jurnal Komunikasi, 2023)
Hashtags are used in digital social movements to mobilize netizens and create social change. This study aims to fill in gaps from previous studies by comparing the hashtags #PercumaLaporPolisi and #PolriSesuaiProsedur, which emerged on Twitter as social movements in response to the rape of three children under ten in East Luwu, South Sulawesi. The study incorporates framing analysis and focuses on the frame alignment process to see the efforts of the hashtags #PercumaLaporPolisi and #PolriSesuaiProsedur on mobilizing social media users. This study uses Social Network Analysis (SNA) to analyze the network structure formed from #PercumaLaporPolisi vs. #PolriSesuaiProsedur hashtags and determine the values of reciprocity, centralization, diameter, density, and modularity. The researcher also uses framing alignment analysis to analyze the tweets collected using Python from October 6-17, 2021, and Netlytic software as a tool. This text compares the effectiveness of two Twitter hashtags, #PercumaLaporPolisi, and #PolriSesuaiProsedur, in mobilizing supporters during a campaign about police policies in Indonesia. Network analysis found that #PolriSesuaiProsedur had a more extensive network, higher density, and more robust framing than #PercumaLaporPolisi, which resulted in a more effective mobilization of supporters. The text emphasizes the importance of precise messaging and framing in hashtag activism. This study compared the success of two hashtags, #PercumaLaporPolisi, and #PolriSesuaiProsedur, and found that #PolriSesuaiProsedur was more successful due to its clear framing. This research highlights the significance of precise framing in hashtags for mobilizing supporters in digital social movements. Future studies could investigate the impact of various hashtags on mobilization.